Validation of the Customer Experience Model of Iran Telecommunication Company from Commercial Sales Towards their Retention - Karehvand , Mohamad; Mahmoodzadeh vashan, Mahdi; Hakimpour, Hosein; Salehnia, Monireh (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: The purpose of this research is to validate the customer experience model of Iran Telecommunication Company in commercial sales towards their retention. Methodology: This study was applied in objective and quantitative in execution with a structural modeling approach. The population in this part of the research included all commercial sales customers of the Telecommunications of Qom province, numbering 1700 individuals. The sample size was determined to be 315 individuals using Morgan’s table and was selected through convenience sampling. The research instrument was a researcher-made questionnaire. The questionnaire’s questions and statements were developed using the research literature, theoretical foundations, and the results of the qualitative study, whose face and content validity was confirmed by experts, and its reliability was obtained with a Cronbach’s alpha method of 0.961. The data were analyzed using the structural equation modeling method in SMART PLS software. Findings: The findings of this research showed that the evolutionary organizational structural model has 19 sub-components within seven prerequisite components of customer experience management, measurement and analysis of customer experiences, service experience, value creation, marketing mix, brand image, and support activities, all of which fit well and all variables obtained can be considered in designing the final model. The effectiveness of each variable was discussed and analyzed in terms of their existence. The results indicated that the prerequisites of customer experience management, measurement and analysis of customer experiences, service experience, value creation, marketing mix, brand image, and support activities were significant in the research model. Conclusion: The results showed that the customer experience model of Iran Telecommunication Company in commercial sales towards their retention is valid.